Ecouri ale Descriptio Moldaviae în scrierile istorico-geografice franceze (secolul al XVIII-lea) - Ileana Mihăilă (Revista de Istorie și Teorie Literară)
This paper analyzes the circulation of Dimitrie Cantemir’s works dedicated to the geography of the Romanian Principalities (most notably the Descriptio Moldaviae, his map of Moldavia and the Historia Moldo-Vlachica), as well as their echoes in certain French geographical and historical writings of the second half of the 18th century, particularly in the works of Jean-Baptiste Bourguignon d’Anville, Louis-Félix Guinement de Kéralio and Charles Léopold Andreu de Bilistein. This research mainly concerns Dacia vetus et nova, a project that has been reconstructed based on the few conserved fragments and their reception, as well as its role in configuring the way the French Enlightenment understood the unity of the three Romanian provinces.